Conjugate margin pattern of the Southwest Sub‐basin, South China Sea: insights from deformation structures in the continent‐ocean transition zone. (5th November 2015) - Ding, Weiwei; Li, Jiabiao
Abstract: Eight cross‐sections from the continent‐ocean transition zone of the Southwest Sub‐basin, South China Sea, have been used to compare conjugate rifted margins that are typical of magma‐poor rift systems. The geological timing of the break‐up unconformity in the continental margins shows that the Reed Bank and the Dangerous Grounds in the south continental margin connect with the Zhongsha Islands and the western Phu Khanh Basin, which experienced northwest‐southeast oriented movement after the opening of the Southwest Sub‐basin. Detailed interpretations identify a range of deformational and sedimentary features in the continent‐ocean transition zones with and without rigid blocks. Remarkable structural similarities appear in the transition zone lying within the convex‐shaped area shaped by rigid blocks of the conjugate margin (e.g. the Zhongsha Islands and the Reed Bank) or within concave‐shaped areas sandwiched by rigid blocks. Rigid tectonic blocks such as the Zhongsha Islands and the Reed Bank played important roles in both the shaping of the continent‐ocean boundary and the initial continental break‐up. Copyright © 2015 John Wiley & Sons, Ltd.